Relationship between Tei Index and Prognosis in Patients with Non ST Segment Elevation Myocardial Infarction - Seyis, Sabri; Ozcan, Turkay (Archives of Clinical and Biomedical Research, 2017)
Background and Objective: It is important to make risk stratification for patients with non ST segment elevation MI to reduce mortality, reinfarctions and to improve prognosis. Through the echocardiographic parameters; ejection fraction does not reflect diastolic functions. Tei index is a new parameter representing both left ventricular systolic and diastolic functions at the same time. The aim of this study is to determine the relationship between Tei index and prognosis in patients with non ST segment elevation MI. Method: Fifty patients (mean age: 60.1±11) with non ST segment elevation MI were included to our study. All the patients were given standard care and managed according to well accepted guidelines. Clinical and laboratry data were collected during hospitalization. Echocardiographic examinations were done on the hospitalization day and 3 months after discharge. Tei index and other echocardiographic examinations were evaluated. Results: Mean value of the index through the patient group was 0.39±0.03, whereas it was 0.59±0.09 through control group (p:0.001). Through the follow up 14 patients (28%) had major cardiac adverse events (MACE). Tei index of deaths were significantly higher than alives (0.73±0.005 vs 0.58±0,09, p:0.002). Compared to uncomplicated patients, the mean Tei index was significantly higher in patients with complications (0.71±0.0 vs0.55±0.07, p:0.001). Death was observed in 4 patients (14.2%) in Tei index 0.60 group whereas no death was seen in Tei index <0.60 group (p:0.001). Heart failure was observed in 10 patients (35.7%) in Tei index 0.60 group compared to only 2 patients (9%) in Tei index <0.60 group (p:0.001). After 3 months, Tei index values were decreased in both groups of patients. Conclusion: It is concluded that Tei index can be